Enhancing the Voice of Youth Program at the Adventist University of the Philippines: An Appreciative Inquiry - NAMANYA , DAN; BUALOY , RESTITUTO; Fernando , Andresito; HERNANDO , JAYLORD; CADAO , CERELITO; Endriga, Danilo (12th International Scholars Conference 2025, 2026)
The Voice of Youth (VOY) program at the Adventist University of the Philippines (AUP) is part of the worldwide Seventh-day Adventist Church initiative, I Will Go, which ensures the involvement of every youth in proclaiming the three angels' messages of Revelation 14:6-12. This program empowers young people in evangelism, leadership, and mission work. To examine ways to sustain and expand its influence, this study explores key strengths, best practices, and opportunities for growth using a qualitative approach, specifically Appreciative Inquiry. The study is also grounded in Transformational Leadership Theory. This study, conducted within the AUP VOY program, gathered data through semi-structured interviews with 11 purposively selected participants and two focus group discussions with VOY members and coordinators. Thematic analysis was applied, using open coding, peer debriefing, and triangulation to ensure reliability. Findings for the Discovery Phase revealed VOY’s role in fostering spiritual growth, community engagement, teamwork, and missionary influence. The Dream Phase envisioned stronger spiritual foundations, improved preparation, and greater faculty involvement, while the Design Phase emphasized training, leadership, financial sustainability, and inclusivity. The Destiny Phase focused on expansion, resource mobilization, and long-term commitment. These insights highlight VOY’s contribution to leadership, evangelism, and institutional support. Strengthening leadership, ensuring financial sustainability, and enhancing institutional backing are crucial for long-term success. Future research should explore VOY’s global influence on youth leadership and mission work.